Nutritional and Rheological Characterization of an Infant Flour Based on Parboiled Rice (Oryza sativa), Spirulina (Spirulina platensis), and Cashew Nut (Anacardium occidentale) - Love Mouka Mahouli; Bruno Fotso Saah; Hygride Dongmo; Justine Odelonne Kenfack; Bilkissou Njapndounke; Marie Madeleine Nanga Ndjang; Mathilde Julie Klang (International Journal of Food Science)
Protein-energy malnutrition and mineral deficiencies in children under five years are major problems in developing countries. The present study was thus carried out with the aim of proposing a weaning flour based on parboiled rice, spirulina, and cashew nut that meets the nutritional needs of children aged 06 to 24 months. To achieve this, the mixture design approach (a 9-point augmented simplex-centroid design) was used to obtain optimal blend of flour. The responses evaluated where proteins, lipids, carbohydrates, minerals (iron, calcium, phosphorus, potassium, sodium, magnesium, and zinc), carotenoids, fibers, and ash content. The rheological analyses (rapid viscosity analysis) were carried out on the optimal flour. It results that the optimal proportion of parboiled rice, spirulina, and cashew nut was, respectively, 85.80, 5.96, and 8.23. These conditions result in a protein, lipids, carbohydrates, carotenoids, ash, fibers, calcium, iron, magnesium, and zinc content of 14.15%, 9.04%, 68.46%, 8.2 mg, 3% ash, 4.98%, 510 mg, 16 mg, 65 mg, and 5 mg, respectively, and an energy value of 411.8 kcal. These optimate conditions resulted also in a peak viscosity of 60 cP and a final viscosity of 86 cP which are lower than the established value (1000 cP). Thus, the weaning flour based on parboiled rice, spirulina, and cashew nut obtained in these optimate conditions can meet the nutritional needs of children aged 06 to 24 months and is therefore an efficient weaning food to fight against child malnutrition.